2017
DOI: 10.1186/s12885-017-3750-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of CD133lo cancer stem cells in Retinoblastoma Y79 cell line

Abstract: BackgroundRetinoblastoma (Rb), the most common childhood intraocular malignant tumor, is reported to have cancer stem cells (CSCs) similar to other tumors. Our previous investigation in primary tumors identified the small sized cells with low CD133 (Prominin-1) and high CD44 (Hyaluronic acid receptor) expression to be putative Rb CSCs using flow cytometry (FSClo/SSClo/CD133lo/CD44hi). With this preliminary data, we have now utilized a comprehensive approach of in vitro characterization of Y79 Rb cell line foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
3
28
1
1
Order By: Relevance
“…We further investigated the expression of CSC-related genes in CRC cells after treatment with Treg supernatants. The results showed that CSC-related gene [25, 26] expression in SW620 and DLD1 cells was significantly lower than that in cells treated with Treg supernatants (Fig. 4d).…”
Section: Resultsmentioning
confidence: 94%
“…We further investigated the expression of CSC-related genes in CRC cells after treatment with Treg supernatants. The results showed that CSC-related gene [25, 26] expression in SW620 and DLD1 cells was significantly lower than that in cells treated with Treg supernatants (Fig. 4d).…”
Section: Resultsmentioning
confidence: 94%
“…Besides glioblastoma, SDF-1/CXCR4 signaling has been shown to be functional in stem(-like) subpopulations of retinoblastoma (60), melanoma (61), pancreatic ductal adenocarcinoma (62), non-small cell lung cancer (63), cervical carcinoma (64), prostate cancer (65), head and neck squamous cell carcinoma (66), rhabdomyosarcoma (67, 68), synovial sarcoma (56), and leukemia (69). In summary, these data might hint to an ontogenetically early onset of SDF-1/CXCR4 signaling in mesenchymal and epithelial primordia of the different organs which might be the reason for SDF-1/CXCR4 expression in stem(-like) subpopulations of many different tumor entities.…”
Section: Sdf-1/cxcr4 Function In Tumor Biologymentioning
confidence: 99%
“…Many tumors contain a small percentage of cancer stem cells, with the ability to self-renew, metastasize, and confer chemoresistance (for review see [21]). Previous work from our group, confirmed by others, has demonstrated the presence of these cancer stem cell markers in human retinoblastoma [22,23,24,25]. We know that in breast cancer, Her2 expression and overexpression is associated with a cancer stem cell phenotype (for Review, see [26]).…”
Section: Discussionmentioning
confidence: 62%